Subject Teacher Education in Transition Educating Teachers for the Future - Ropo, Eero; Jaatinen, Riitta (Tampere University Press, 2020)
This edited book introduces the development, theories and practices of subject teacher education in the subject didactic context at the University of Tampere, Finland, during the last 25-30 years. The authors are teacher educators and researchers, representing educational sciences, foreign languages, mother tongue, art education, mathematics and science, or social science teacher education. The purpose of the book is to introduce readers with theoretical foundations, directions and results of the development from the perspective of the future of teaching and teacher education.